PENERAPAN ETIKA MORALITAS DAN BUDAYA MALU DALAM MEWUJUDKAN KINERJA PEGAWAI NEGERI SIPIL YANG PROFESIONAL - Tobirin Tobirin (Jurnal Manajemen Kepegawaian, 2008)
Existence of PNS become keyword from taking place an state especially in service of public. Big role which is accountability this civil servant make civil servant required by society and have to domicile strategic in life of have state and go into society. But along with the role of strategic of civil servant confronted by various problem embosoming, of low performance storey;level, and ethics of morality which not yet been woke up, low prosperity storey;level, ill defined career ladder, and reward , construction and observation . Various this problems become bureaucracy reform starting point to improve;repair performance of aparatur bureaucracies. One other primal are how to apply ashamed culture in bureaucracy. Role of humanist a leader needed especially to give example to his him. Beside that in improve;repairing performance of civil servant this is needed stages;steps, like repair of system of rekruitmen, punisment and reward the fairness, clear and coherent law, slogan civil servant , correcting political system. Keyword : performance, cultural of shame, leader.